Uncovering thousands of endosymbiont DNA transfer events within single cockroach genomes - Kyle M. Ewart; Maxim W. D. Adams; Zhuzhi Zhang; Louise Baker; Kokuto Fujiwara; Yoshinobu Hayashi; Leo A. Featherstone; Oscar Lo Lu; Jil E. S. Helbling; Maya Moral; Kiyoto Maekawa; Harley Rose; et al. (Proceedings of the National Academy of Sciences, 2026)
Horizontal gene transfer (HGT) between organisms can be a valuable source of genetic variation and innovation. Research on HGT in eukaryotes has hitherto focused on transfers of coding sequences; insertions of noncoding DNA remain poorly understood. Here, we investigated HGT in cockroaches, which have a long-standing evolutionary relationship with the transovarially transmitted endosymbiont Blattabacterium cuenoti , making them a valuable system for assessing the potential scale of HGT. We aligned 150-bp genomic fragments of B. cuenoti to 23 cockroach and termite genomes, including 8 genomes newly sequenced, and revealed pervasive endosymbiont DNA transfer events. Australian panesthiine and geoscapheine cockroaches were consistently found to harbor >3000 HGT inserts, more than an order of magnitude higher than the previous maximum estimate in other eukaryotes, excluding rotifers. Some inserts appear to have persisted for ≥28.7 million years in this group, which may reflect functional roles. We identified numerous chimeric inserts comprising up to nine short segments from different locations in the B. cuenoti genome. Our findings indicate pervasive HGT in eukaryote genomes, with potentially far-reaching implications for adaptation and speciation.